THE EFFECT OF SOCIAL MEDIA ON COMMUNITY SOCIAL CHANGE - Khaeriyah Khaeriyah; Anne Abdul Rahman; Indriati Amirullah; Idham Gentanegara; Nurasia Natsir (Pusat Riset dan Inovasi Nasional, 2023)
Indonesia is one of the many countries with confirmed cases of Covid-19. An increase in Covid-19 cases can have a big impact, one of the impacts is the declining quality of human resources for each individual in a company. To improve the quality of human resources, of course you have to know the management of human resources. Human resource management is the process of managing human beings from planning, recruitment, selection, training, development, compensation, career, safety, health and maintaining industrial relations to termination of employment to achieve from the company and achieve prosperity. The scope of HRM is the objectives of HRM, policy objectives and functions of HRM related to improving the quality of the company's human resources, including: 1. Planning 2. Organizing 3. Implementation 4. Supervision. The functions of human resource management in a company or organization itself include: 1. Job analysis 2. Human resource planning 3. Human resource recruitment 4. Selection 5. Training and development 6. Job evaluation 7. Compensation 8. Career path 9. Safety and health. Factors that influence the quality of human resources in a company are as follows: 1. Company culture 2. Environment 3. Technology 4. Leadership 5. Adaptation 6. Productivity 7. Motivation and recognition. The company's strategy in order to improve the quality of human resources after Covid-19, as follows: 1. Clear job description 2. Detailed work planning 3. Emphasis on technical qualifications and skills 4. Emphasis on special worker training 5.